Indian Telecommunications Industry: Awareness about telecom in users and their assessment of affordability of telecom services - Singh, Netra Pal; Mishra, Pankaj; Farooq, Ayesha (Industrija, 2020)
It has been 25 years since India announced its first telecom policy called the National Telecom Policy in 1994. Since then the Indian Telecommunications Industry has witnessed tremendous growth. At a teledensity of 89.92% (May 2019), it is the second largest telecom market in the world. The policy maker (DoT)[1] and the regulator (TRAI)[2] have taken several initiatives to achieve the vision of “secure, reliable, affordable and high-quality converged telecommunication services anytime, anywhere”. TRAI also drives an objective of creating increased level of awareness about telecom among the Indian subscribers. Through a structured survey and analysis of data thus collected, this study presents an objective assessment of awareness about TRAI and DoT and affordability of telecom services among Indian subscriber. The study further analyses the relationship between user’s awareness and their assessment of affordability of telecom users. We found half of the surveyed users aware of DoT. But more than half were aware of TRAI and about Indian governments vision for telecommunications. 85% of survey respondents find telecom services affordable, however the level of affordability varies across gender, age group and educational qualification. Female users find telecom services less affordable compared to male. This defeats the objective of equal access and the Indian government’s vision of telecom for all. Since our regression analysis indicated that awareness influences user’s assessment of affordability, it is recommended that TRAI and DoT take actions to increase the level of awareness about telecom among users. This will help in furthering the objective of affordability where uses may choose services based on their level of affordability. In addition affordability of female users can be addressed through customized tariff plan and schemes. [1] DoT: Department of Telecommunications, India [2] TRAI: Telecom Regulatory Authority of India